2021
DOI: 10.1002/aic.17504
|View full text |Cite
|
Sign up to set email alerts
|

Divided‐wall distillation column design using molecular tracking

Abstract: Divided-wall column (DWC) is an intensified separation process and so far developing a simple procedure for designing these units has been challenging. In this work, the concept of molecular tracking has been integrated with conventional methods to build a simple and easy-to-use methodology for designing DWCs for multicomponent separations. Application of the proposed approach is highlighted through several three-and four-component mixtures. The configuration obtained using molecular tracking gives a design wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 26 publications
(37 reference statements)
1
16
0
Order By: Relevance
“…From Table 2, it can be observed that the configuration obtained by using FPBB is very similar to the configuration in the literature (Montonati et al, 2022). The method used in the literature (Montonati et al, 2022) is a special procedure, which requires short-cut models to determine the initial design parameters of DWC, followed by equilibriumstaged simulation, molecular tracking application and finally using many simulations to investigate the effects of varying parameters in the flowsheet to find an optimal design. The design procedure is tailored without generality and computationally intensive for design of DWC.…”
Section: Example 1: Separation Of N-pentane N-hexane and N-heptanesupporting
confidence: 54%
See 4 more Smart Citations
“…From Table 2, it can be observed that the configuration obtained by using FPBB is very similar to the configuration in the literature (Montonati et al, 2022). The method used in the literature (Montonati et al, 2022) is a special procedure, which requires short-cut models to determine the initial design parameters of DWC, followed by equilibriumstaged simulation, molecular tracking application and finally using many simulations to investigate the effects of varying parameters in the flowsheet to find an optimal design. The design procedure is tailored without generality and computationally intensive for design of DWC.…”
Section: Example 1: Separation Of N-pentane N-hexane and N-heptanesupporting
confidence: 54%
“…These two configurations are rather different. From Table 5, we can see that the total number of trays obtained from the FPBB algorithm is 135, which is 28 more than 106 in the literature (Montonati et al, 2022). The larger number of stages results in a smaller reflux ratio and less energy consumption in both condenser and reboiler.…”
Section: Example 2: Separation Of N-butane I-pentane N-pentanementioning
confidence: 91%
See 3 more Smart Citations